Decoupling of nutrient stoichiometry in Suaeda glauca (Bunge) senesced leaves under salt treatment - Yang, Fugui; Liu, Shuang; Qian, Ma; Wang, Donger; Chen, Jihui (Frontiers in Plant Science, 2023)
The stoichiometry of senesced leaves is pivotalSenesced leaves stoichiometry plays a crucial role in nutrient cycling, and can be significantly influenced by soil salinization, a rising global issue threatening the functionality of ecosystemswhich can be altered by soil salinization, a growing global concern threatening ecosystem function. However, The the impactsimpacts of soil salinization on senesced leaves leaf stoichiometry are not fully understoodstoichiometry, however, remain unclear. In this study, we conducted a pot experiment with varying soil salt concentrations to examine their influencedetermine their effect on the concentrations and stoichiometric ratios of nitrogen (N), phosphorus (P), sodium (Na), potassium (K), calcium (Ca), magnesium (Mg) and zinc (Zn) in the senesced leaves of Suaeda glauca (Bunge) senesced leaves. Compared to the control group, salt treatments significantly enhancedincreased Na concentration while diminishing but decreased the concentrations of K, Ca, Mg, Zn, N, and P. Interestingly, However, as salinity levels escalated increased, N concentration maintained stabilityremained stable, whereasbut P concentration exhibitedshowed an increasing trend. Moreover,Furthermore, K, Ca, and Mg significantly declined as salt levels rosewith increasing salt levels. Salt treatments brought about significant changes in significantly altered stoichiometric ratios, with the decrease of N:P, K:Na, N:Na, N:Mg and Ca:Mg ratios dropping, and thebut increase of N:Ca and N:K ratios rising, illustrating the varying nutrient coupling cycles under different salt conditions, reflecting the different coupling cycling of these nutrients in different salt conditions. These findings shed light onresults reveal that the plasticity of This is a provisional file, not the final typeset article stoichiometric traits in S. glauca senesced leaves in response to soil salinization shifts, stoichiometric traits of Suaeda glauca (Bunge) senesced leaves with change of soil salinization, which could potentially offer insights into nutrient cycling reactions to soil salinization.with potential implications for understanding nutrient cycling responses to soil salinization.